2007
DOI: 10.1016/j.cardiores.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of Rho-kinase improves cardiac contractile function in streptozotocin-diabetic rats

Abstract: Objective: The purpose of the present study was to determine whether increased activation of the RhoA/Rho-kinase (ROCK) pathway occurs in diabetic cardiomyopathy and whether acute inhibition of this pathway improves contractile function of the diabetic heart. Methods: Male Wistar rats were made diabetic with streptozotocin. Twelve to fourteen weeks later, the effects of acute administration of the ROCK inhibitors Y-27632 and H-1152 on cardiac contractile function were measured both in vitro, in isolated workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 38 publications
6
63
0
Order By: Relevance
“…We hypothesized that the Rho/ROCK signaling pathway may be involved in the increase in visfatin and type I procollagen levels, since previous studies have shown a role for this pathway in chronic fibrosis of the liver and kidney (19,25), and that it is activated in the heart of diabetic rats (21,22). The present study showed that high-glucose treatment increased the expression levels of ROCK1, visfatin and type I procollagen in CFs from newborn rats.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We hypothesized that the Rho/ROCK signaling pathway may be involved in the increase in visfatin and type I procollagen levels, since previous studies have shown a role for this pathway in chronic fibrosis of the liver and kidney (19,25), and that it is activated in the heart of diabetic rats (21,22). The present study showed that high-glucose treatment increased the expression levels of ROCK1, visfatin and type I procollagen in CFs from newborn rats.…”
Section: Discussionsupporting
confidence: 55%
“…The Rho/ROCK signaling pathway is implicated in chronic fibrosis of the liver and kidneys (19,20). Previous studies showed that the ROCK pathway is also activated in the cardiac cells of rats with diabetes (21,22). The expression of the Ras homolog gene family, member A (RhoA) protein was upregulated and its activity was enhanced, resulting in increased polymerization of the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…ROCK regulates not only the actin cytoskeleton but also the expression of genes associated with tissue fibrosis [10,34] . Data from some studies [35,36] suggest diabetes impairs cardiac function through upregulation of RhoA. The increase in RhoA expression and activity in diabetic hearts resulted in increased phosphorylation of ROCK targets, LIM kinase and ezrin/radixin/moesin, leading to an increase in actin polymerization which might be associated with cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Two isoforms of ROCK, ROCK1 and ROCK2, have been identified, and both are widely expressed (38). Overactivation of the RhoA-ROCK pathway has been implicated in the development of many forms of cardiovascular disease, including hypertension, heart failure, and diabetic cardiomyopathy (26). Increased ROCK activity has also been detected in the heart and other tissues from obese, insulin-resistant animal models (25) and in leukocytes from patients with metabolic syndrome (27).…”
mentioning
confidence: 99%